Effect of processing on physical characteristics, handling properties and utilization of wheat middlings - Fahrenholz, C.H.; Allee, G.L.; Eustace, D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Wheat middlings were pelleted and ground through different types of grinders. The resulting products were incorporated into finishing pig diets and a digestion trial was conducted to determine the effect of processing on nutrient utilization. Pelleting and grinding midds prior to use in pelleted finishing diets improved pelleting throughput and efficiency. Results of the digestion study showed there were no detrimental effects on nutrient utilization because of processing. This, along with reduced shipping costs and improved handling characteristics, indicate that pelleting wheat midds at the flour mill would be beneficial to the feed industry and could result in lower feed costs for the swine producer.
Keywords: Swine; Processing; Wheat middlings